Development and optimization of the activated charcoal suspension composition based on a mixture design approach - Ronowicz Joanna; Kupcewicz Bogumiła; Pałkowski Łukasz; Krysiński Jerzy (Acta Pharmaceutica)
In this study, a new drug product containing activated charcoal was designed and developed. The excipient levels in the pharmaceutical formulation were optimized using a mixture design approach. The adsorption power of the activated charcoal suspension was selected as the critical quality attribute influencing the efficacy of medical treatment. Significant prognostic models (p < 0.05) were obtained to describe in detail the interrelations between excipient levels and the adsorption power of the formulation. Liquid flavour had a critical impact on the adsorption power of the suspension. Formulations containing the largest amount of liquid flavour showed the lowest adsorption power. Sorbitol was not adsorbed onto activated charcoal so strongly as liquid flavour. A slight increase in the content of carboxymethylcellulose sodium led to a marked decrease in adsorption power. The obtained mathematical models and response surface allowed selection of the optimal composition of excipients in a final drug product